Antimicrobial resistance in the Eastern Mediterranean Region: experiences, challenges, and perspectives - Al Bakri, Deema; Joukhadar, Maya; Ikram, Aamer; Motriuc, Nelea; Matar, Ghassan M.; Ghanem, Rola Ali; Mahrous, Heba; Taha, Tariq Hassan; Ahmad, Hafiz; Muthu, Priyalatha; Al Faouri, Ibrahim; Bashier, Haitham; et al. (Frontiers in Public Health, 2025)
Antimicrobial resistance (AMR) is a rapidly growing global health threat that undermines the effectiveness of first-line treatments for serious infectious diseases. During the Eighth Regional Conference of the Eastern Mediterranean Public Health Network (EMPHNET), held in Amman, Jordan, from September 15–18, 2024, this critical issue took center stage under the theme “Advancing Public Health Preparedness and Response.” A dedicated roundtable discussion on AMR explored the challenges of implementing effective AMR surveillance, the widespread misuse of antibiotics, and the urgent need for a One Health approach that integrates human, animal, and environmental health. Speakers emphasized that political commitment, sustainable funding, and cross-sector collaboration are essential to curbing AMR, particularly in the Eastern Mediterranean Region (EMR), where factors such as high antimicrobial consumption, conflict, weak health systems, and poor access to regulated antibiotics exacerbate the problem. The discussion also highlighted the critical roles of laboratories and infection prevention and control (IPC) programs in healthcare settings, both of which are central to AMR surveillance and stewardship. Global efforts, including the WHO’s Global Action Plan on AMR and the AMR Multi-Stakeholder Partnership Platform, were recognized as vital frameworks for fostering international cooperation and guiding regional responses. The roundtable concluded with a call for strengthened governance, enhanced laboratory capacities, improved surveillance systems, scaling up IPC programs and enhanced public awareness campaigns to confront the rising threat of AMR in the EMR.